La semántica del deseo: Lenguaje e interpretación (2016)
The present essay stems from the interplay between language and interpretation in psychoanalysis, subject that becomes clearer in this article through the understanding of what Paul Ricoeur labels “The Semantics of Desire”. Questioning the language and the interpretation according to Ricoeur and Freud, allows the semantic structure that flags desire to be explored. It demonstrates the privileged place that the word has in psychoanalysis, as well as its link to that which constitutes the peculiarity of the subject of the unconscious. A rather complex matter, this has generated several dialogues between various disciplines, which is even more true when one adds to it the range of interpretation possible regarding words that reveal a hidden content and that are particular to each subject.